A teacher between the center and the periphery. Jelica Belović- Bernadzikowska’s path to emancipation in the “Memoirs” - Panas, Natalia (Poznańskie Studia Slawistyczne, 2024)
Jelica Belović-Bernadzikowska (1870–1946) was an ethnologist, writer and pedagogue. In her Memoari (Memoirs), she describes the beginnings of the education system under the Habsburg monarchy in Bosnia and Hercegovina, and her own contribution to pedagogical development, despite its hierarchical and discriminatory structure. The Memoirs show the emergence of the emancipatory process, the paths of a woman’s independent thought, and the impact of the changes she introduces. I analyze The Memoirs, modestly discussed, and show what a working woman faced in the education system in the 19th century – I place the text on the center-periphery axis in the perspective of cultural memory.